Análise da evolução do plano estratégico de tecnologia da informação em um banco público brasileiro: um estudo de cinco anos - Torres, Sabrina Morais Coelho (2024)
This study examines the evolution of the Information Technology (IT) Strategic Plan in a Brazilian public bank over a five-year period, employing a methodology that combines bibliographic and documentary research. The bibliographic research focused on reviewing specialized literature on public banks, strategic management and innovation, and the development of master plans in public institutions. Concurrently, the documentary research analyzed official bank documents, including annual reports and previous master plans. The findings indicate considerable progress in the management and operationalization of IT in the bank, highlighted by the restructuring of the IT area with a focus on product vision, the creation of business towers with multidisciplinary teams, and improvements on contracting third-party services. The analysis also revealed the importance of innovation and adaptation to the rapid changes in the financial sector, with the adoption of modern solutions over obsolete systems. However, areas for improvement were identified, such as inconsistencies in SWOT analysis and in setting goals for indicators, as well as challenges related to compliance with legislation and the retention of qualified talent. The study underscores the need for holistic and adaptive IT governance, emphasizing the execution of an ever-evolving master plan to keep the institution competitive and innovative.